2018
DOI: 10.1039/c8cc01054d
|View full text |Cite
|
Sign up to set email alerts
|

Folding polymer chains with visible light

Abstract: We introduce a mild and efficient avenue to induce the folding of single chain polymer nanoparticles (SCNPs) using visible light. The versatility of the method is based on three folding mechanisms exploiting tetrazole chemistry, i.e., nitrile imine-mediated tetrazole-ene cycloaddition (NITEC), nitrile imine carboxylic acid ligation (NICAL) as well as nitrile imine self-dimerization. To our knowledge, this visible light driven approach is the to-date mildest avenue to fold single polymer chains into compact par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…For photoinduced chemical bond formation, commonly high‐energy UV light is required, which often leads to photodamage especially when employed in biological systems. Even when going to longer wavelengths and into the visible range, often high intensities are required to obtain acceptable reaction rates . Recently, our team introduced a styrylpyrene functionalized PMMA system that exploits the proximity effect of a preformed polymer to significantly increase the quantum efficiency of the [2 + 2] photocycloaddition of styrylpyrene forming a single chain nanoparticle .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For photoinduced chemical bond formation, commonly high‐energy UV light is required, which often leads to photodamage especially when employed in biological systems. Even when going to longer wavelengths and into the visible range, often high intensities are required to obtain acceptable reaction rates . Recently, our team introduced a styrylpyrene functionalized PMMA system that exploits the proximity effect of a preformed polymer to significantly increase the quantum efficiency of the [2 + 2] photocycloaddition of styrylpyrene forming a single chain nanoparticle .…”
Section: Methodsmentioning
confidence: 99%
“…Even when going to longer wavelengths and into the visible range, often high intensities are required to obtain acceptable reaction rates. [26] Recently, our team introduced a styrylpyrene functionalized PMMA system that exploits the proximity effect of a preformed polymer to significantly increase the quantum efficiency of the [2 + 2] photocycloaddition of styrylpyrene [27] forming a single chain nanoparticle. [28] We therein demonstrated that 80% conversion after 24 h of exposure to laboratory light was readily achievable (with an illuminance given of 624 lux).…”
Section: Wwwadvancedsciencenewscom Wwwmrc-journaldementioning
confidence: 99%
“…Additionally, photogenerated collapse induced by UV irradiation of external bis-azide-containing aggregation induced emission (AIE) cross-linkers has been employed by De La Cuesta and Pomposo [42] as a fast and efficient method to produce highly fluorescent SCNPs. Recently, SCNPs have been additionally prepared through photogenerated collapse using external cross-linkers via photoinduced NICAL [37] and via photoinduced nitroxide radical-α-hydroxyalkyl phenyl ketone coupling [54]. Figure 15.…”
Section: Synthesis Of Single-chain Polymer Nanoparticles Via Photogenmentioning
confidence: 99%
“…36 Other photochemical pathways for chain compaction include dimerization, 37,38 or the utilization of light-induced generation of highly reactive species for crosslinking. 39,40 Critically, to the best of our knowledge, there exists no example of SCNPs that exploit the combination of visible lightinduced chemistry and oxime ester derivatives to induce the formation of single-chain folded structures. Thus, we herein designed a photoreactive styrene derivative, which is tethered to a pyrene-substituted oxime ester (PyOHSty).…”
mentioning
confidence: 99%